“It's more than just a conversation about the heart”: exploring barriers, enablers, and opportunities for improving the delivery and uptake of cardiac neurodevelopmental follow-up care - Abell, Bridget; Rodwell, David; Eagleson, Karen J.; Parsonage, William; Auld, Ben; Bora, Samudragupta; Kasparian, Nadine A.; Justo, Robert; McPhail, Steven M. (Frontiers in Pediatrics, 2024)
Surveillance, screening, and evaluation for neurodevelopmental delays is a pivotal component of post-surgical care for children with congenital heart disease (CHD). However, challenges exist in implementing such neurodevelopmental follow-up care in international practice. This study aimed to characterise key barriers, enablers, and opportunities for implementing and delivering outpatient cardiac neurodevelopmental follow-up care in Australia. Materials and methods: an exploratory descriptive qualitative study was conducted with healthcare professionals across Australia who had lived experience of designing, implementing, or delivering neurodevelopmental care for children with CHD. Online semi-structured interviews were conducted using a guide informed by the Consolidated Framework for Implementation Research to explore contextual influences. Interview transcripts were analysed using a rapid qualitative approach including templated summaries and hybrid deductive-inductive matrix analysis. Results: fifty-two participants were interviewed. Perceived barriers and enablers were organised into six higher-order themes: factors in the broader environmental, economic, and political context; healthcare system factors; organisational-level factors; provider factors; patient and family factors; and care model factors. The largest number of barriers occurred at the healthcare system level (service accessibility, fragmentation, funding, workforce), while service providers demonstrated the most enabling factors (interprofessional relationships, skilled teams, personal characteristics). Strategies to improve practice included building partnerships; generating evidence; increasing funding; adapting for family-centred care; and integrating systems and data. Summary: Australia shares many similar barriers and enablers to cardiac neurodevelopmental care with other international contexts. However, due to unique geographical and health-system factors, care models and implementation strategies will require adaption to the local context to improve service provision.